ANALISIS LITERASI KEUANGAN PELAKU UMKM DI DESA DALUNG, KECAMATAN KUTA UTARA, KABUPATEN BADUNG - Pramitari, I G A Astri; Nurhayanti, Ketut; Abdi, Normandewi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.12.NO.02.TAHUN.2023DO - 10.24843/EEB.2023.v12.i02.p15, 2023)
The COVID-19 pandemic had an impact on the micro, small and medium enterprises (MSME) sector. MSMEs' understanding of Financial Literacy can help MSMEs survive in this difficult time. This study aims to determine the level of financial literacy of MSMEs in Dalung Village, North Kuta District, Badung Regency. This study was conducted to analyze whether differences in gender, age, and level of education have a significant effect on the level of financial literacy of MSME owners. The company used in this study is a trading company, with a sample of 40 MSME owners. The research method used is a survey method by obtaining data through a questionnaire that has been tested for validity and reliability. The results showed that the level of financial literacy of MSME owners was less literate (60%). The variable that affects the level of financial literacy is the level of education, while differences in gender and age have no effect on the level of financial literacy of the owners of MSMEs.